Abstract: Fiducial Marker Recovery and Detection From Severely Truncated Data in Navigation-Assisted Spine Surgery - Fan, Fuxin; Kreher, Björn W.; Keil, Holger; Maier, Andreas; Huang, Yixing (Bildverarbeitung für die Medizin 2023, 2023)
Fiducial markers are commonly used in navigation-assisted minimally invasive spine surgery and they help transfer image coordinates into real-world coordinates. In practice, these markers might be located outside the field-of-view (FOV) of C-arm cone beam computed tomography (CBCT) systems. As a consequence, reconstructed markers in CBCT volumes suffer from artifacts and have distorted shapes, which sets an obstacle for navigation. In this work, we propose two fiducial marker detection methods: direct detection from distorted markers (direct method) and detection after marker recovery (recovery method) [1]. For direct detection from distorted markers in reconstructed volumes, an efficient automatic marker detection method using two neural networks and a conventional circle detection algorithm is proposed. For marker recovery, a task-specific data preparation strategy is proposed to recover markers from severely truncated data. Afterwards, a conventional marker detection algorithm is applied for position detection. The networks in both methods are trained only on simulated data and the two methods are evaluated on simulated data and real cadaver data. The direct method achieves 100% detection rates within 1 mm detection error on simulated data with normal truncation and simulated data with heavier noise, but only detect 94.6% markers in extremely severe truncation case. The recovery method detects all the markers successfully in three test data sets and around 95% markers are detected within 0.5 mm error. For real cadaver data, both methods achieve 100% marker detection rates with mean registration error below 0.2 mm. Our experiments demonstrate that the direct method is capable of detecting distorted markers accurately and the recovery method with the task-specific data preparation strategy has high robustness and generalizability on various data sets. The task-specific data preparation is able to reconstruct structures of interest outside the FOV from severely truncated data better than conventional data preparatio
Keywords: Data truncation; Deep learning; CBCT; Spine surgery; Fiducial marker

Analysis of remaining motion using one innovative upper airway opening cervical collar and two traditional cervical collars - Jung, Matthias K.; von Ehrlich-Treuenstätt, Gregor V.R.; Keil, Holger; Grützner, Paul A.; Schneider, Niko R.E.; Kreinest, Michael (Scientific Reports, 2021)
The aim of this study was to compare the remaining motion of an immobilized cervical spine using an innovative cervical collar as well as two traditional cervical collars. The study was performed on eight fresh human cadavers. The cervical spine was immobilized with one innovative (Lubo Airway Collar) and two traditional cervical collars (Stifneck and Perfit ACE). The flexion and lateral bending of the cervical spine were measured using a wireless motion tracker (Xsens). With the Weinman Lubo Airway Collar attached, the mean remaining flexion was 20.0 ± 9.0°. The mean remaining flexion was lowest with the Laerdal Stifneck (13.1 ± 6.6°) or Ambu Perfit ACE (10.8 ± 5.8°) applied. Compared to that of the innovative Weinmann Lubo Airway Collar, the remaining cervical spine flexion was significantly decreased with the Ambu Perfit ACE. There was no significant difference in lateral bending between the three examined collars. The most effective immobilization of the cervical spine was achieved when traditional cervical collars were implemented. However, all tested cervical collars showed remaining motion of the cervical spine. Thus, alternative immobilization techniques should be considered.
CRIS-Team Scopus Importer:2021-10-29

Automated Digital Image Optimisation in Intraoperative 2D and 3D Imaging Using a Mobile C-Arm With Flat-Panel Detector - Groh, Johannes; Perl, Markus; Bräuer, Lars; Stadthalter, Holger (International Journal of Medical Robotics and Computer Assisted Surgery, 2025)
Background: Assistance tools for intraoperative 2D and 3D imaging to decrease acquisition effort and to improve assessment of 3D image data were evaluated. Methods: Two automated optimisation procedures were evaluated in a cadaver (Cios Spin, Siemens, Germany): The ScrewScout function for assisted pedicle screw assessment. Then, an algorithm for metal artefact reduction (MAR). Additionally, a tool for simplified setting of image contrast and brightness was evaluated regarding the result and elapsed time. Results: The time required without automated assistance was 83s [70–105]. With the computer assistance, this time was significantly lower at 22s [15–32] (p = 0.003). MAR resulted in an improvement in image impression. This improvement became smaller with increasing clinical experience. The time needed for setting of image acquisition parameters was significantly (p = 0.05) lowered from 140s [24–389] to 61s [14–166] using the assistance tool. Conclusions: Automated assistance tools for image optimisation can provide practical support in the intraoperative setting.
CRIS-Team Scopus Importer:2025-03-14
Keywords: automated image analysis; intraoperative imaging; MAR; metal artifact reduction; ScrewScout; SpotAdapt

Automatic Plane Adjustment in Surgical Cone Beam CT-volumes - Martín Vicario, Celia; Kordon, Florian; Denzinger, Felix; Weiten, Markus; Thomas, Sarina; Kausch, Lisa; Franke, Jochen; Keil, Holger; Maier, Andreas; Kunze, Holger (Informatik aktuell, 2021)
CRIS-Team Scopus Importer:2021-04-19

Automatic Plane Adjustment of Orthopedic Intraoperative Flat Panel Detector CT-Volumes - Martín Vicario, Celia; Kordon, Florian; Denzinger, Felix; Weiten, Markus; Thomas, Sarina; Kausch, Lisa; Franke, Jochen; Keil, Holger; Maier, Andreas; Kunze, Holger (Medical Image Computing and Computer Assisted Intervention – MICCAI 2020, 2020)
Flat panel computed tomography is used intraoperatively to assess the result of surgery. Due to workflow issues, the acquisition typically cannot be carried out in such a way that the axis aligned multiplanar reconstructions (MPR) of the volume match the anatomically aligned MPRs. This needs to be performed manually, adding additional effort during viewing the datasets. A PoseNet convolutional neural network (CNN) is trained such that parameters of anatomically aligned MPR planes are regressed. Different mathematical approaches to describe plane rotation are compared, as well as a cost function is optimized to incorporate orientation constraints. The CNN is evaluated on two anatomical regions. For one of these regions, one plane is not orthogonal to the other two planes. The plane’s normal can be estimated with a median accuracy of 5°, the in-plane rotation with an accuracy of 6°, and the position with an accuracy of 6 mm. Compared to state-of-the-art algorithms the labeling effort for this method is much lower as no segmentation is required. The computation time during inference is less than 0.05 s.<br
Keywords: Orthopedics; Flat planel CT; Multiplanar reconstruction

Cervical Spine Immobilization in Patients With a Geriatric Facial Structure: The Influence of a Geriatric Mandible Structure on the Immobilization Quality Using a Cervical Collar - Jung, Matthias K.; Grützner, Paul A.; Schneider, Niko R.E.; Keil, Holger; Kreinest, Michael (Geriatric Orthopaedic Surgery and Rehabilitation, 2021)
Introduction: Demographic changes have resulted in an increase in injuries among geriatric patients. For these patients, a rigid cervical collar is crucial for immobilizing the cervical spine. However, evidence suggests that patients with a geriatric facial structure require a different means of immobilization than patients with an adult facial structure. This study aimed to analyze the remaining motion of the immobilized cervical spine based on facial structure. Materials and Methods: This study was performed on 8 fresh human cadavers. Facial structure was evaluated via ascertaining the mandibular angle by computer tomography. A mandibular angle below 130°, belongs to the adult facial structure group (n = 4) and a mandibular angle above 130°, belongs to the geriatric facial structure group (n = 4). The flexion and lateral bending of the immobilized cervical spine were analyzed in both groups using a wireless motion tracker system. Results: A flexion of up to 19.0° was measured in the adult facial structure group. The mean flexion in the adult vs. geriatric facial structure groups were 14.5° vs. 6.5° (ranges: 9.0-19.0 vs. 5.0-7.0°), respectively. Thus, cervical spine motion was (p = 0.0286) significantly more reduced in the adult facial structure group. No (p = 0.0571) significant difference was oberserved in the mean lateral bending of the adult facial structure group (14.5°) compared to the geriatric facial structure group (7.5°). Conclusion: Emergency medical service personnel should therefore follow current guidelines and recommendations and perform cervical spine immobilization with a cervical collar, including in patients with a geriatric facial structure.
CRIS-Team Scopus Importer:2021-06-18
Keywords: cervical collar; cervical spine; geriatric facial structure; immobilization quality

Combined Odontoid (C2) and Atlas (C1) Fractures in Geriatric Patients: A Systematic Review and Treatment Recommendation - Spiegl, Ulrich J.A.; Keil, Holger; Krause, Julia; Osterhoff, Georg; Scheyerer, Max J.; Schnake, Klaus John; Perl, Mario (Global Spine Journal, 2023)
Study Design: Systematic review. Objective: The aim of this study was to conduct a systematic overview of the pathogenesis and the treatment options of combined odontoid and atlas fractures in geriatric patients. Methods: This review is based on articles retrieved by a systematic search in the PubMed and Web of Science databases for articles published until February 2021 dealing with combination fractures of C1 and C2 in geriatric patients. Results: Altogether, 438 articles were retrieved from the literature search. A total of 430 articles were excluded. The remaining eight original articles were included in this systematic review depicting the topics pathogenesis, non-operative treatment, posterior approach, and anterior approach. The overall level of evidence of the studies is low. Conclusion: Combined odontoid and atlas fractures in the geriatric population are commonly caused by simple falls and seem to be associated with atlanto-odontoid osteoarthritis. Non-operative treatment with a cervical orthosis is a feasible treatment option in the majority of patients with stable C2 fractures. In case of surgery posterior C1 and C 2 stabilization and anterior triple or quadruple screw fixation are possible techniques. Some patients may also deserve an occipito-cervical fusion. A possible treatment algorithm is proposed.
CRIS-Team Scopus Importer:2023-05-05

Comparison of T-POD and SAM Pelvic Sling II and the influence of attachment level in the initial management of unstable pelvic type C injuries – a cadaveric study - Privalov, Maxim; Junge, Malte; Jung, Matthias Karl; Vetter, Sven Yves; Franke, Jochen; Hetjens, Svetlana; Grützner, Paul Alfred; Stadthalter, Holger (International Journal of Emergency Medicine, 2024)
Background: Type C pelvic fractures (AO/OTA) are severe injuries that frequently lead to bleeding and hemodynamic instability. Pelvic binders play a crucial role in their initial management. Placement at the correct level in the prehospital setting is challenging. The aim of this study was to compare two pelvic binders regarding their effectiveness in reducing intrapelvic volume and increasing intrapelvic pressure in patients with type C pelvic fractures (AO/OTA) when applied at three different levels. Methods: Rotationally and vertically unstable pelvic injuries (AO/OTA classification 61-C1.1) were produced in five fresh-frozen human cadaveric specimens. Intrapelvic volume, vesical pressure and compression pressure within the pubic symphysis and the sacroiliac joint were measured when applying a SAM Pelvic Sling II and a T-POD at the level of the greater trochanter as well as levels higher and lower than recommended. Results: Comparison of the two pelvic binders positioned at the recommended level (greater trochanter) showed no significant difference in volume reduction (13.85 ± 31.37 cm3, p = 0.442), however, increase in vesical pressure was significantly higher when using the T-POD (5.80 ± 3.27 cmH2O, p = 0.017). When positioned at the level of the iliac crest, vesical pressure increase and intrapelvic volume reduction were significantly greater with the T-POD (14.00 ± 8.57 cmH2O, p = 0.022 and 10.45 ± 5.45 cm3, p = 0.031 respectively). Application of the SAM Pelvic Sling II below the greater trochanter led to a significantly greater decrease in volume (-32.26 ± 7.52 cm3, p = 0.003) than the T-POD. Comparison of the recommended attachment level with incorrect positioning led to no significant differences for the T-POD, while the SAM Pelvic Sling II achieved a significantly lower volume reduction when placed at the iliac crest (40.15 ± 14.57 cm3, p = 0.012) and a significantly lower increase in vesical pressure when applied below the greater trochanter (3.40 ± 1.52 cmH2O, p = 0.007). Conclusion: Direct comparison of the two pelvic binders showed that the T-POD achieved significantly greater results when applied at the recommended level and was less susceptible to incorrect positioning. These outcomes support the preferred use of the T-POD for prehospital emergency pelvic stabilisation.
CRIS-Team Scopus Importer:2024-03-15
Keywords: Pelvic binder; Pelvic fracture; Pelvic stabilization; SAM pelvic Sling II; T-POD; Unstable pelvic Injury

Early Outcomes of Pelvic Trauma Patients - Complications, ICU Stay and Treatment Concepts in Two ATLS Compliant Trauma Centers: Germany and Qatar - Keil, Holger; El-Menyar, A.; Daerr, J.; Weil, F.; Abdelrahman, H.; Alhammoud, A.; Ghouri, S.; Babikir, E.; Wahlen, B. M.; Al-Thani, H.; Gruetzner, P. A.; Muenzberg, M. (Acta Chirurgiae Orthopaedicae Et Traumatologiae Cechoslovaca, 2021)
PURPOSE OF THE STUDY
CRIS-Team WoS Importer:2022-06-17

Evaluation of external stabilization of type II odontoid fractures in geriatric patients—An experimental study on a newly developed cadaveric trauma model - Jung, Matthias K.; von Ehrlich-Treuenstätt, Gregor V.R.; Jung, Andreas L.; Keil, Holger; Grützner, Paul A.; Schneider, Niko R.E.; Kreinest, Michael (PLoS ONE, 2021)
Background Along with the growing geriatric population, the number of odontoid fractures is steadily increasing. However, the effectiveness of immobilizing geriatric odontoid fractures using a cervical collar has been questioned. The aim of the present study is to analyze the physiological and pathological motion in odontoid fractures and to assess limitation of motion in the cervical spine when applying a cervical collar. Methods Motion analysis was performed with wireless motion tracker on unfixed geriatric human cadavers. First, a new geriatric type II odontoid fracture model was developed. In this model, the type II odontoid fracture is operated via a transoral approach. The physiological and pathological flexion and lateral bending of the cervical spine resulting from this procedure was measured. The resulting motion after external stabilization using a cervical collar was analyzed. Results The new geriatric type II odontoid fracture model was successfully established using seven unfixed human cadavers. The pathological flexion of the cervical spine was significantly increased compared to the physiological flexion (p = 0.027). Furthermore, the flexion was significantly reduced when a cervical collar was applied. In case of flexion the mean remaining motion was significantly reduced (p = 0.0017) from 41° to 14°. For lateral bending the mean remaining motion was significantly reduced (p = 0.0137) from 48° to 18°. Conclusions In case of type II odontoid fracture, flexion and lateral bending of the cervical spine are increased due to spinal instability. Thus, if an odontoid fracture is suspected in geriatric patients, the application of a cervical collar should always be considered since external stabilization can significantly reduce flexion and lateral bending.
CRIS-Team Scopus Importer:2021-12-10

Evaluation of image quality and assessability of a new flat-panel 3D C-arm compared to mobile and fixed computed tomography in posterior spinal fixation - Keil, Holger; Luxenhofer, Miriam; Vetter, Sven Y.; Beisemann, Nils; Grutzner, Paul A.; Franke, Jochen (International Journal of Medical Robotics and Computer Assisted Surgery, 2020)
Background This study evaluates image quality of a new flat-panel three-dimensional (3D) C-arm to the current generation and to intraoperative and stationary computed tomography (CT) in spinal surgery.
CRIS-Team WoS Importer:2020-11-20

Fiducial marker recovery and detection from severely truncated data in navigation assisted spine surgery - Fan, Fuxin; Kreher, Björn W.; Keil, Holger; Maier, Andreas; Huang, Yixing (Medical Physics, 2022)
Purpose: Fiducial markers are commonly used in navigation assisted minimally invasive spine surgery and they help transfer image coordinates into real world coordinates. In practice, these markers might be located outside the field-of-view (FOV) of C-arm cone-beam computed tomography (CBCT) systems used in intraoperative surgeries, due to the limited detector sizes. As a consequence, reconstructed markers in CBCT volumes suffer from artifacts and have distorted shapes, which sets an obstacle for navigation. Methods: In this work, we propose two fiducial marker detection methods: direct detection from distorted markers (direct method) and detection after marker recovery (recovery method). For direct detection from distorted markers in reconstructed volumes, an efficient automatic marker detection method using two neural networks and a conventional circle detection algorithm is proposed. For marker recovery, a task-specific learning strategy is proposed to recover markers from severely truncated data. Afterwards, a conventional marker detection algorithm is applied for position detection. Results: The two methods are evaluated on simulated and real data. The direct method achieves 100% detection rates with maximal 2-pixel difference on simulated data with normal truncation and simulated data with severe noise, but fails to detect all the markers in extremely severe truncation case. The recovery method detects all the markers successfully with maximal 1 pixel difference on all simulated data sets. For real data, both methods achieve 100% marker detection rates with mean registration error below 0.2 mm. Conclusions: Our experiments demonstrate that the direct method is capable of detecting distorted markers accurately and the recovery method with task-specific learning has high robustness and generalizability on various data sets. The task-specific learning is able to reconstruct structures of interest outside the FOV from severely truncated data, which has the potential to empower CBCT systems with new applications.<br
Keywords: minimally invasive spine surgery; marker detection; marker recovery; task-specific learning; truncation correction

Intraoperative Computed Tomography in Orthopaedic Trauma Surgery - Keil, Holger; Vetter, Sven Y.; Gruetzner, Paul Alfred; Franke, Jochen (Zeitschrift für Orthopädie und Unfallchirurgie, 2021)
Background When using mobile 3D C-arms, impairments in image quality occur due to artefacts caused by metal implants as well as to the limited field of view. To avoid these restrictions, special computed tomography devices were designed, in order to improve image quality and to meet requirements for intraoperative usage.
CRIS-Team WoS Importer:2021-05-21

Intraoperative revision rates due to three-dimensional imaging in orthopedic trauma surgery: results of a case series of 4721 patients - Keil, Holger; Beisemann, Nils; Swartman, Benedict; Schnetzke, Marc; Vetter, Sven Yves; Gruetzner, Paul Alfred; Franke, Jochen (European Journal of Trauma and Emergency Surgery, 2022)
Purpose: Intraoperative 3D imaging has become a valued tool in assessing the quality of reduction and implant placement in orthopedic trauma surgery. In our institution, 3D imaging is used routinely since 2001. To evaluate the intraoperative findings and consequences of this technique, intraoperative revision rates in cases with 3D imaging were analyzed. Methods: All operative procedures carried out with intraoperative 3D imaging between August 2001 and December 2016 were included. The scans were assessed intraoperatively and documented thereafter. In case of malreduction or misplaced implants, an immediate revision was performed. The number of scans per case as well as the findings and consequences drawn regarding the anatomical region were analyzed. Results: 4721 cases with 7201 3D scans were included in this study. The most common anatomical regions were the ankle (22.3%), the calcaneus (14.8%) and the tibial head (9.5%). In 19.1% of all cases, an intraoperative revision was performed. The highest revision rates were found with 36.0% in calcaneal fractures, 24.8% in fractures of the tibial plateau, 22.3% in injuries of the ankle. In 52.0% of revisions, the reduction was improved regarding intra-articular steps or joint congruency. In 30.5% an implant was corrected. Conclusion: Intraoperative revision due to results of 3D imaging was performed in almost one-fifth of cases. This illustrates the improved possibilities to detect malreduction and implant misplacements intraoperatively and thus the abilities to improve surgical outcome. Level of evidence: III.
CRIS-Team Scopus Importer:2022-09-16
Keywords: 3D imaging; Fractures; Intraoperative imaging; Osteosynthesis

Precision and effort in robot-assisted placement of pedicle screws compared to standard surgical navigation - Sippel, Julia Katharina; Groh, Johannes; Bräuer, Lars; Perl, Mario; Stadthalter, Holger (Scientific Reports, 2024)
Aim was to compare image-guided navigation with a robot-assisted solution for performing MISS regarding precision, required time and subjective aspects. 90 pedicles were instrumented on two torsos, half with navigation, half robot-assisted. Precision analysis between both solutions didn’t show a significant difference. Time measurement showed a significantly longer duration per wire for the robot-arm on the first torso and a not significant longer duration on the second torso, where a significant reduction in the mean duration was shown. There was no significant difference in the subjective impressions comparing navigation and robot except the possibility to change the procedure. Precision of both methods is suitable for clinical use. A time advantage using the robot-arm couldn’t be demonstrated in the present study. A significant learning curve was shown, so a reduction in the longer duration on the robot can be expected. Further studies in clinical use are necessary.
CRIS-Team Scopus Importer:2024-11-22